TERMS AS THE BASIS OF SCIENTIFIC AND TECHNICAL TRANSLATION ON THE EXAMPLE OF TERMINOLOGY OF SECURITY SYSTEMS (Academicia Globe: Inderscience Research, 2023)
Translation of technical literature has a number of distinctive features. The language of scientific literature is characterized by brevity and accuracy of wording. Adding a term to the dictionary helps you capture the meaning of the term. Dictionaries allow you to avoid confusion when translating texts of scientific literature. The terminology should be systematic and have a common meaning. Terms allow you to define the semantic structure, as well as the features of the terminology object.